Sistem Informasi Jasa Laundry Berbasis Web Pada Cemerlang Laundry - Tarigan, Apriyani Ripka Yustika Br; Marbun, Nasib (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Cemerlang Laundry is a company engaged in the field of laundry services in Ujung Serdang Village. The number of customers who use Cemerlang Laundry services continues to increase. However, the processing of laundry service data at Cemerlang Laundry is still using a conventional ledger data recap system. So that it causes a continuous accumulation of files which can make it difficult for Cemerlang Laundry employees to search for certain files quickly and easily when needed. The purpose of the study was to determine the procedure for managing laundry service data at Cemerlang Laundry, design a web-based laundry service information system at Cemerlang Laundry and build a web-based laundry service information system at Cemerlang Laundry. With this, it is necessary to have tools to build a laundry service information system such as PHP: Hypertext Preprocessor, MySQL, and Sublime Text. The results of this study conclude that the web-based laundry service information system implemented is able to help solve the problems that occur in the Cemerlang Laundry business, so a tool is needed in the form of a computerized information system.